PENGARUH METODE QUANTUM TEACHING TERHADAP HASIL BELAJAR SISWA KELAS 1 BIDANG KEAHLIAN TEKNIK BANGUNAN GEDUNG DI SMKN 3 SEMARANG - Widodo, Aris (Universitas Negeri Semarang, 2009)
This research aims at: (1) explaining the difference of achievement as a result of conventional method and Quantum Teaching Method, (2) describing the relationship of positive dependence attitude between QuantumTeaching and students achievement. The research method was Quasi Experiment with percentage approach. The population was the first grade students of SMKN 3 Semarang majoring in Construction Engineering in the academic year of 2005/2006. The dependent variable was Quantum Teaching Method (X), while the independent variable was the students achievement (Y). The data were gathered through documentation, questionnaire, and test method. Man Whitney experiment and regression analysis was used to analyze the data for the first hypothesis. It was found that there was a significant difference between students who studied with Quantum Teaching method and those who studied with conventional method. Students who studied with Quantum Teaching Method performed better than those who studied with the conventional method. The regression analysis which examined the second hypothesis showed that there was a significant relationship between the students positive dependent attitude and their study achievement.Kata Kunci : quantum teaching, teknik bangunan, dan kompetensiMTBG